Assessing the Potential of Brewer’s Spent Grain to Enhance Cookie Physicochemical and Nutritional Profiles - Marisa Nicolai; Maria Lídia Palma; Ricardo Reis; Rúben Amaro; Jaime Fernandes; Elsa M. Gonçalves; Mafalda Silva; Manuela Lageiro; Adília Charmier; Elisabete Maurício; Patrícia Branco; Carla Palma; et al. (Foods)
Brewers’ spent grain (BSG), the major by-product of the brewery industry, has high nutritional value, making it suitable for upcycling into products such as healthy, and sustainable cookies. Nonetheless, the incorporation of BSG in cookies can impact their quality, given the increased fiber and protein content. This work explored the effect of replacing wheat flour with BSG at 50% and 75% in cookie formulations, focusing on physical, chemical, and sensory properties. The dietary fiber, lipid, and protein content of cookies improved considerably with the highest incorporation of BSG, increasing from 6.37% to 15.54%, 9.95% to 13.06%, and 9.59% to 12.29%, respectively. Conversely, moisture and water activity decreased from 11.03% to 3.37% and 0.742 to 0.506, respectively, forecasting a lower risk of microbial contamination and increased shelf-life. The incorporation of BSG in cookies resulted in decreased brightness and increased hardness, from 40 N to 97 N. Moreover, colorimetric shifts among the control cookies and the two BSG-rich formulations could be easily identified by an untrained observer. Sensory evaluation showed that cookies with 50% BSG retained acceptable sensory characteristics, suggesting potential for further development. Overall, BSG enhances the nutritional profile of cookies with no excessive detrimental impact on sensory features.